Hållbart ansvarstagande för ett medelstort byggföretag i Sverige - En analys av värdeskapande aktiviteter som bidrar till hållbar utveckling. - Gustafsson, Emelie; Nylander, Anna (My University, 2013)
This report deals with activities that from a CSR perspective are considered to create a shared value for a medium-sized construction company in Sweden. The CSR definition used in the report is the European Commission’s since it reflects the valuecreating aspects of CSR, in contrast to the traditional philanthropic aspect of CSR. Companies in the building construction industry have difficulties identifying activities that create value in society and in the company. The aim with the project is to, from a CSR perspective, identify and evaluate value creating activities in a building construction company. The activities will be evaluated with respect to competitiveness and how they can be implemented into an organization. The activities chosen are in line with the industries sustainability challenge and to Wäst-Bygg, the result of the evaluation will be a list of relevant CSR activities that are in line with the company’s culture and logic. The project was conducted through literature studies and a comparison based on a mapping of the largest building construction companies in Sweden. Good examples outside the industry were used to generate options on how the industry can be further developed. An analytical framework was applied to the industries’ building construction companies to identify and analyze today’s activities the industry. Special attention is given to Wäst-Bygg on value creating CSR activities that can be used in future development and increased competitiveness on the market. The main results show that the differences between the construction industry and the good examples are how the company perceives the product lifecycle, how knowledge and knowledge transfer is valued and the monitoring of CSR on the company. A company’s change process to realize a value creating CRS in a company, management commitment, clear goals, visions and open and fair communication is important.
Keywords: Energi; Hållbar utveckling; Geovetenskap och miljövetenskap; Annan naturvetenskap; Miljöbioteknik; Annan teknik; Energy; Sustainable Development; Earth and Related Environmental Sciences; Other Natural Sciences; Environmental Biotechnology; Other Engineering and Technologies